Amino Acid Ester based Phenolic Ionic Liquids as a Potential Solvent for the Bioactive Compound Luteolin: Synthesis, Characterization, and Food Preservation Activity - Shimul, I.M. (Elsevier B.V., 2022)
Ionic liquids (ILs) have gained great attention as potent solubilizing agents of poorly soluble bioactive compounds. The use of Luteolin (LUT) â a natural bioactive compound â is limited because of its poor aqueous solubility. To address this issue, this study reports potential ILs for effectively solubilizing LUT at ambient temperature. First, promising ILs were screened from a potential 180 ILs that were proposed by the combination of 20 standard amino acid ethyl esters cations and nine phenolic acids anions using the conductor-like screening model for real solvents (COSMO-RS); the activity coefficients of LUT at infinite dilution in ILs were used as the screening criteria. Four proline ethyl ester phenolate ILs (PEEP-ILs) composed of a biocompatible proline ethyl ester and bioactive phenolic acids (trans-ferulic, vanillic, p-coumaric, and 4-hydroxybenzoic acid) were selected and synthesized. The synthesized PEEP-ILs were characterized through 1H NMR, FT-IR, elemental analysis, TGA, and DSC. The experimental solubility of LUT in PEEP-ILs (60 IL in water) showed excellent solubility. Among the PEEP-ILs, proline ethyl ester ferulate (ILProEtFer) exhibited the best LUT solubility, followed by ILs with p-coumarate (ILProEtCou), vanillate (ILProEtVan), and 4-hydroxybenzoate (ILProEtBen). 1H NMR assessment and COSMO-RS prediction confirmed that the ILs facilitated the solubilization of LUT through multiple hydrogen bonding, Ï â Ï, and cation â Ï interactions between the LUT and the ILs. The biocompatibility study revealed that PEEP-ILs were relatively harmless and low toxicity compared with conventional imidazolium, pyridinium, pyrrolidinium, piperidinium, and morpholinium-based ILs. The LUT dissolved in the newly-synthesized PEEP-ILs and demonstrated better organoleptic properties on red apple slices. These results indicate that PEEP-ILs can be potential green alternatives to conventional toxic solvents for dissolving poorly water-soluble bioactive natural preservatives. Â© 2021 Elsevier B.V.